The spatial effects of rural toilet retrofitting investment on farmers' medical and health expenditure in China - Zheng, Xin; Yang, Fu-Xia; Fan, Dong-Shou; Yang, Zao-Ning (Frontiers in Public Health, 2023)
The effect of China’s toilet renovation work is still unbalance across regions, and adjusting the investment strategy will help to improve the health of rural residents. Although existing studies have focused on the spatial heterogeneity of rural toilet renovation work, the spatial correlation caused by inter-subject learning imitation and factor market competition has been ignored by scholars. In this study, the spatial econometric model is used to analyze the spatial effect that toilet renovation investment has on farmers’ medical and health expenditure from the perspectives of spatial heterogeneity and spatial correlation. The results reveal that (1) there are significant spatial agglomeration characteristics of the toilet renovation investment and farmers’ medical and health expenditure in China. (2) In the whole country, the total, direct and indirect effects of rural toilet renovation investment on the farmers’ medical and health expenditure are significantly negative, and the direct effect is greater than the indirect effect. (3) The total effect on toilet renovation investment is in the following order: central > eastern > western, and that of northeast is not significant. The direct effect is in the following order: central > eastern > western > northeast. Improving the farmers’ health in the eastern and central regions by investing in toilet renovation would lead to imitation by neighboring regions, thus causing spillover effects. Toilet renovation investment in western China would lead to fierce competition in related industries and factor markets, which is manifested as a competition effect. (4) The spillover effect is found in the four regions, and its intensity is the greatest in the central and western regions, followed by west–northeast; the influence in east–west and east–northeast is not significant. Therefore, the comprehensive promotion of rural toilet renovation work should not only focus on investment in the western and northeastern regions but also need to strengthen regional exchange and cooperation, the overall planning and coordinated development of human settlements.